Cryptocurrency sebagai aset digital dalam perspektif maqashid syariah: Analisis antara spekulasi dan investasi halal - Novie Andriani Zakariya; Adi Basuki Choirul; Kholid Albar; Dimas Wahyu Rozaki; Mukhamad Roni; Syahrul Ulum; Mochammad Wafiyul Ahdi (universitas Islam Zainul Hasan Genggong, 2026)
Cryptocurrency has emerged as a digital asset that raises debates in Islamic economics regarding its legality and compliance with Maqasid al-Shariah principles. Previous studies mainly focused on the legal and technical aspects of cryptocurrency, while limited research comprehensively examines it through the Maqasid al-Shariah framework. This study aims to analyze whether cryptocurrency can be categorized as a Shariah-compliant investment or speculative practice prohibited in Islam. This research employs a qualitative approach using library research methods through the analysis of academic literature, fatwas, and relevant documents. The findings indicate that cryptocurrency has the potential to become a Shariah-compliant financial instrument if supported by real economic value, transparent governance, and proper regulation. However, excessive speculation, market volatility, and anonymity remain major challenges that may contradict Islamic principles of wealth protection and social justice. Therefore, a Maqasid-based regulatory and screening framework is needed to ensure cryptocurrency operates in accordance with Shariah values.